Techniques for noise robustness in automatic speech recognition - Virtanen, Tuomas; Singh, Rita.; Raj, Bhiksha; Wiley eBooks (Chichester, West Sussex, U.K. : Wiley, 2012)
"Automatic speech recognition (ASR) systems are finding increasing use in everyday life. Many of the commonplace environments where the systems are used are noisy, for example users calling up a voice search system from a busy cafeteria or a street. This can result in degraded speech recordings and adversely affect the performance of speech recognition systems. As the use of ASR systems increases, knowledge of the state-of-the-art in techniques to deal with such problems becomes critical to system and application engineers and researchers who work with or on ASR technologies. This book presents a comprehensive survey of the state-of-the-art in techniques used to improve the robustness of speech recognition systems to these degrading external influences."--
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Automatic speech recognition; COMPUTERS -- Optical Data Processing; Automatic speech recognition; Electronic books